2017
DOI: 10.1515/sem-2016-0188
|View full text |Cite
|
Sign up to set email alerts
|

Greimas embodied: How kinesthetic opposition grounds the semiotic square

Abstract: According to Greimas, the semiotic square is far more than a heuristic for semantic and literary analysis. It represents the generative “deep structure” of human culture and cognition which “define the fundamental mode of existence of an individual or of a society, and subsequently the conditions of existence of semiotic objects”. The veracity of this bold hypothesis has received little attention in the literature. In response, this paper traces the history and development of the square of opposition from Aris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Greimas (1987). The weight of this possibility in turn would be augmented by the embodied relations of the four-limbed Yama who supports it; and this orientation might provide evidence for testing my hypothesis that the semiotic square is itself an embodied diagram (Pelkey, 2017a). With this hypothesis in mind, I began to wonder whether or not different tokens of this model were robustly consistent in terms of their internal organization between part-whole relations or, alternatively, whether they might be marked by substantial variation.…”
Section: Case Study 2: Comparative Yama Bhavachakra Mandalasmentioning
confidence: 94%
“…Greimas (1987). The weight of this possibility in turn would be augmented by the embodied relations of the four-limbed Yama who supports it; and this orientation might provide evidence for testing my hypothesis that the semiotic square is itself an embodied diagram (Pelkey, 2017a). With this hypothesis in mind, I began to wonder whether or not different tokens of this model were robustly consistent in terms of their internal organization between part-whole relations or, alternatively, whether they might be marked by substantial variation.…”
Section: Case Study 2: Comparative Yama Bhavachakra Mandalasmentioning
confidence: 94%
“…It is not to discourage questioning and investigation in stories from the marginalized communities; to the contrary, the project encourages fair criticism of all sources. Western imperial knowledge creates "psychological double-binds" (Pelkey, 2017), and misses opportunities that demand critical examination (Alatas, 2000;Pelkey, 2017). The project presents a diversity of stories that were excluded from the binary logic due to ideological difference and connects to the universal human experience in the pandemic.…”
Section: Methodsmentioning
confidence: 99%
“…In his study on the semiotic square, Pelkey suggested to engage in peaceful dialogue and obtain universal knowledge inquiry, it is important to abandon the double-bind approach in any ideological architecture that presuppose one member of the pair having privilege over the other unmarked member, in social or intellectual status (2017). The "oppositional tautology" (Pelkey, 2017) in the semiotic square can be used to illustrate The National's ideologically driven presentation of China and consideration for information in the middle-ground. The vacuum video space in the project is charged with power discourse and can be seen as spatial dimensions in the semiotic square with oppositional relationship of top/bottom and left/right.…”
Section: Projectmentioning
confidence: 99%
See 1 more Smart Citation
“…The semiotic or Greimas square could be treated as a type of extended dichotomies. Scholars apply the semiotic square by analyzing human cognition [43], heuristic aspects of social existence [44], educational process [45], (anti)brand meanings [46] and even Western astrology [47]. Besides this, it has been used in literary criticism [48].…”
Section: Introductionmentioning
confidence: 99%